Platform Leadership and Sustainable Competitive Advantage: The Mediating Role of Ambidextrous Learning - Yang, Xiao; Jin, Rong; Zhao, Changyi (Frontiers in Psychology, 2022)
In the context of the knowledge economy, the role of traditional leadership for enterprises is questioned. Based on contingency theory and the resource-based view, this paper proposes the important role of platform leadership, a new leadership type in line with the context of the times, for a sustainable competitive advantage. We conducted an empirical study to examine and confirm the positive effects of platform leadership on sustainable competitive advantage and ambidextrous learning. We also verified the mediation effect of exploratory and exploitative learning on platform leadership and sustainable competitive advantage. Additionally, relevant discussion and research contributions are put forward.